2020
DOI: 10.1177/1475472x20905053
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of 3-D finlets using Reynolds-averaged Navier–Stokes computational fluid dynamics for trailing edge noise reduction

Abstract: This paper uses Reynolds-averaged Navier–Stokes computational fluid dynamics to study trailing edge noise reduction with 3-D finlets. Reynolds-averaged Navier–Stokes computational fluid dynamics provides boundary layer parameters near a trailing edge for an empirical wall pressure spectrum model, and then an acoustic model predicts far-field noise based on pressure fluctuations obtained from the wall pressure spectrum model. First, this numerical approach is validated against experiments. Second, a comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…These mean and r.m.s. velocity profiles are consistent with the velocity profiles obtained from finlet fences in previous experimental and numerical studies (see Afshari et al [28], Shi and Lee [30], and Bodling and Sharma [29]). A phenomenon analogous to that described by [31] as a 'lift-up of energy carrying eddies' seems therefore to take place here, which increases the separation distance between source and scattering edge, and reduces the noise production efficiency [29].…”
Section: Flow Around Finlet Railssupporting
confidence: 90%
See 1 more Smart Citation
“…These mean and r.m.s. velocity profiles are consistent with the velocity profiles obtained from finlet fences in previous experimental and numerical studies (see Afshari et al [28], Shi and Lee [30], and Bodling and Sharma [29]). A phenomenon analogous to that described by [31] as a 'lift-up of energy carrying eddies' seems therefore to take place here, which increases the separation distance between source and scattering edge, and reduces the noise production efficiency [29].…”
Section: Flow Around Finlet Railssupporting
confidence: 90%
“…Also, the spanwise coherence decreases for length scales larger than the fences spacing, which attenuates TE noise at the mid-frequencies. Shi and Lee [30] found that the surface treatment retards the flow in the finlet channels, with a reduction of the turbulent kinetic energy at the wall. The recent study of Ananthan and Akkermans [31] identifies several interconnected noise reduction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…According to the need for a noise prediction method for the flow field results, the Reynolds-averaged Navier-Stokes (RANS) method is used for the flow field numerical calculation. The k ω − shear stress transport (SST) turbulence model is used in the flow field calculation, which is capable of solving the rotating flow, secondary flow, and boundary layer separation [24,25]. Due to the simulation of the rotor rotation, the computational domain is divided into the rotor domain and stator domain, and the computational domain is divided into four parts (as shown in Figure 3).…”
Section: Aerodynamic Simulation By Ransmentioning
confidence: 99%
“…Lastly, the finlet-spacing to boundary layer thickness ratio was found to be a critical parameter for achieving optimum surface pressure power spectral density reduction. Shi et al [31] conducted a comprehensive trend analysis of finlets. The effects of height, spacing, thickness, position and incoming flow velocity were considered.…”
Section: Surface Finletsmentioning
confidence: 99%
“…Computational aeroacoustics (CAA) simulations simultaneously calculate the hydrodynamic and acoustic fields. This can be done using direct numerical simulations (DNS) [52] or using high fidelity flow simulations coupled with acoustic noise propagation models [31,[53][54][55]. Since noise is nothing but pressure fluctuations that reach the observer, explicitly solving the governing equations of fluid flow is the most accurate numerical approach available.…”
Section: Aerodynamic Noise Predictionmentioning
confidence: 99%